Spatial and temporal patterns of indicators of climate change and variability in the Arab world in the past four decades - Salahuddin M. Jaber; Mahmoud M. Abu-Allaban; Raja Sengupta (Scientific Reports, 2023)
Abstract A comprehensive assessment of the spatial and temporal patterns of the most common indicators of climate change and variability in the Arab world in the past four decades was carried out. Monthly maximum and minimum air temperature and precipitation amount data for the period 1980–2018 were obtained from the CHELSA project with a resolution of 1 km2, which is suitable for detecting local geographic variations in climatic patterns. This data was analyzed using a seasonal-Kendall metric, followed by Sen’s slope analysis. The findings indicate that almost all areas of the Arab world are getting hotter. Maximum air temperatures increased by magnitudes varying from 0.027 to 0.714 °C/decade with a mean of 0.318 °C/decade while minimum air temperatures increased by magnitudes varying from 0.030 to 0.800 °C/decade with a mean of 0.356 °C/decade. Most of the Arab world did not exhibit clear increasing or decreasing precipitation trends. The remaining areas showed either decreasing or increasing precipitation trends. Decreasing trends varied from −0.001 to −1.825 kg m−2/decade with a mean of −0.163 kg m−2/decade, while increasing trends varied from 0.001 to 4.286 kg m−2/decade with a mean of 0.366 kg m−2/decade. We also analyzed country-wise data and identified areas of most vulnerability in the Arab world.